Knockdown of cathepsin D in zebrafish fertilized eggs determines congenital myopathy. Issue 2 (4th April 2013) - Follo, Carlo; Ozzano, Matteo; Montalenti, Claudia; Santoro, Massimo Mattia; Isidoro, Ciro
Abstract : CD (cathepsin D) is a ubiquitous lysosomal hydrolase involved in a variety of pathophysiological functions, including protein turnover, activation of pro-hormones, cell death and embryo development. CD-mediated proteolysis plays a pivotal role in tissue and organ homoeostasis. Altered expression and compartmentalization of CD have been observed in diseased muscle fibres. Whether CD is actively involved in muscle development, homoeostasis and dystrophy remains to be demonstrated. Zebrafish ( Danio rerio ) is emerging as a valuable ' in vivo ' vertebrate model for muscular degeneration and congenital myopathies. In this work, we report on the perturbance of the somitic musculature development in zebrafish larvae caused by MPO (morpholino)-mediated silencing of CD in oocytes at the time of fertilization. Restoring CD expression, using an MPO-non-matching mutated mRNA, partially rescued the normal phenotype, confirming the indispensable role of CD in the correct development and integrity of the somitic musculature. This is the first report showing a congenital myopathy caused by CD deficiency in a vertebrate experimental animal model.